Peningkatan Prestasi Belajar IPA Dengan Strategi Mengoptimalkan Media Gambar Dan Audiovisual Di Kelas V SDIT Harapan Bunda Purwokerto - Suryandari, Anggun (Universitas Sebelas Maret, 2020)
The paper describe about result from classroom action research is based on the low student learning scores on science subject on grade V SDIT Harapan Bunda Purwokerto. The author tries to examine the causes of the low students achievement and find a problem solving. The subject matter of this study is guite simple, namely the optimization strategy of image and audio visual media to determine the improvement of student learning result in science subject about blood circulation. This research was carried out in two cycles that were preceded by a pre-cycle, carried out in September 2016. Cycle 1 was carried out on September 5, 2016 and cycle 2 wa carried out on September 26, 2016. In the first and second cycles, the strategy used was the strategy of optimizing image media and audiovisual media. The result showed an increase student achievement. It is evident from the average valueof class in the initial conditions is 70,0, in the first cycle is 76,2 and the second cycle is 88,1